Dry-method double-layer sulfide electrolyte membrane, preparation method and solid-state battery
Through the preparation method of dry double-layer sulfide electrolyte membrane, the problem of microcracks and polytetrafluoroethylene reduction reaction of dry electrolyte membrane is solved by pressurized composite polymer protective layer and sulfide ion transport layer, and high ionization is achieved Conductivity and stability improve the performance of solid-state batteries.
Patent Information
- Application Number
- CN202411284653.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-07
AI Technical Summary
The existing dry sulfide electrolyte membrane is prone to microcracks during the preparation process, and the polytetrafluoroethylene used may undergo a reduction reaction at low voltage, affecting the performance of the battery cell, and the solvents and binders introduced by the wet process affect Conductivity.
By adopting the preparation method of a dry double-layer sulfide electrolyte membrane, the polymer protective layer is pressurized by combining the polymer protective layer with the sulfide ion transport layer, and the polymer protective layer is polyethylene oxide, polycaprolactone, polymethyl methacrylate, etc. After mixing with the lithium salt, heat and melting, the sulfide ion transport layer is prepared by grinding and rolling treatment, avoiding the use of solvents and binders.
The preparation of electrolyte membranes with low thickness, complete structure, high ionic conductivity and stable interface is achieved, which avoids the reduction reaction of microcracks and polytetrafluoroethylene, and improves the performance and stability of the battery cell.
Smart Images

Figure CN119275331A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a dry-process double-layer sulfide electrolyte membrane, a preparation method thereof, and a solid-state battery. Background Art
[0002] In recent years, the new energy battery industry has developed rapidly, and solid-state lithium batteries with high energy density and safety have become a research hotspot. Sulfide solid electrolytes are considered to be the most promising route for the commercial application of all-solid-state batteries because of their excellent ionic conductivity and good processing performance.
[0003] As the core component of all-solid-state batteries, sulfide electrolyte membranes are generally required to have high ionic conductivity (>1mS / cm) and interface stability. The common sulfide electrolyte membrane preparation processes currently include wet film forming process and dry film forming process. The wet film forming process mainly disperses sulfide in a pre-dissolved gel to form an electrolyte slurry, which is then coated and dried. Sulfide electrolytes have poor chemical stability and are prone to react with solvents and binders during the wet preparation process, thereby affecting the performance of the electrolyte membrane. In addition, electrolyte membranes prepared by wet methods are generally unable to achieve self-support, which requires the addition of an electrolyte transfer and compounding process during the battery cell assembly process, reducing the efficiency of battery cell assembly. The common dry film making process at present mainly involves mixing a binder and an electrolyte and then pressing them to the desired thickness through a hot roller. However, in order to shorten the ion transmission path and improve the performance of the battery cell, the thickness of the solid electrolyte layer is generally required to be less than 30μm. When the electrolyte membrane is pressed to a thinner thickness through a dry preparation process, microcracks are prone to appear on the surface of the electrolyte membrane. The presence of microcracks can cause the battery cell to short-circuit during subsequent assembly and use, resulting in battery cell failure. In addition, the polytetrafluoroethylene (PTFE) used in the dry electrolyte membrane will undergo a reduction reaction at low voltage (negative electrode side), ultimately affecting the performance of the battery cell.
[0004] The invention patent with application publication number CN117832595A discloses a double-layer sulfide electrolyte film and a dry-wet mixing process preparation method. The double-layer sulfide electrolyte film adopts a dry-wet mixing process to prepare a double-layer electrolyte to avoid the reaction of PTFE on the negative electrode side. However, the double-layer sulfide electrolyte film does not solve the problem of microcracks in the current dry electrolyte membrane, and the solvent and binder introduced in the subsequent wet process will have a certain impact on the conductivity of the electrolyte membrane. The invention patent with application publication number CN118016982A discloses a solid electrolyte membrane, a preparation method and a lithium-ion battery. The solid electrolyte membrane is provided with a polymer layer on the negative electrode side by an in-situ polymerization method to solve the problem that PTFE in the solid electrolyte is unstable to the negative electrode. However, the solid electrolyte membrane is coated with a polymer precursor on the surface of the prepared sulfide electrolyte layer. The monomer, initiator, etc. in the polymer precursor will react with the sulfide electrolyte, thereby affecting the overall performance of the electrolyte layer. Summary of the invention
[0005] The first object of the present invention is to provide a dry double-layer sulfide electrolyte membrane to solve the technical problem that the solvent and initiator introduced during the preparation of the existing electrolyte membrane affect the performance of the electrolyte membrane.
[0006] The second object of the present invention is to provide a method for preparing a dry double-layer sulfide electrolyte membrane.
[0007] The third object of the present invention is to provide a solid-state battery.
[0008] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0009] A method for preparing a dry double-layer sulfide electrolyte membrane is provided, wherein a polymer protective layer and a sulfide ion transport layer are compounded under pressure to obtain the membrane, wherein the polymer protective layer is obtained by mixing a polymer and a lithium salt and then heating and melting the mixture.
[0010] Furthermore, the thickness of the polymer protective layer is 1 to 25 μm, and the thickness of the sulfide ion transport layer is 10 to 80 μm.
[0011] Furthermore, the polymer is one or more of polyethylene oxide, polycaprolactone, polymethyl methacrylate, and polyurethane, and the mass ratio of the polymer to the lithium salt is 50-80:20-50.
[0012] Furthermore, the temperature of the heating and melting is 60-120° C., and the pressure of the pressurized compounding is 0.2-10 MPa.
[0013] Furthermore, the preparation method of the sulfide ion transport layer is: mixing sulfide electrolyte powder and dry binder to obtain mixed powder, grinding and fiberizing the mixed powder to obtain a preliminary electrolyte sheet, and rolling the preliminary electrolyte sheet with a roller press.
[0014] Furthermore, the dry binder is polytetrafluoroethylene, and the mass ratio of the sulfide electrolyte powder to the dry binder is 95-99.99:0.01-5.
[0015] Furthermore, the temperature of the upper roller of the roller press is 60-150°C, and the temperature of the lower roller of the roller press is 60-150°C; the rotation speed of the upper roller of the roller press is 0.02-0.15m / min, and the rotation speed of the lower roller of the roller press is 0.02-0.15m / min; the distance between the upper roller of the roller press and the lower roller of the roller press gradually decreases; and the grinding time is 10-90min.
[0016] Furthermore, the lithium salt is one or more of LiTFSI, LiFSI, LiPF6, LiClO4, LiBF4, LiAsF6, LiBOB, and LiODFB, and the sulfide electrolyte is Li2P2S6, Li7P3S 11 , Li3PS4, Li7PS6, Li4P2S6, Li2GeS3, Li4GeS4, Li2ZnGeS4, Li 4-2x Zn x GeS4, Li5GaS4, Li 4+x+y (Ge 1-y-x Ga x )S4、Li 10 SiP2S 12 、Li6PS5K、Li 10 SnP2S 12 , Li 10 GeP2S 12 One or more of, K is a halogen.
[0017] A dry double-layer sulfide electrolyte membrane is prepared by using the above-mentioned preparation method of the dry double-layer sulfide electrolyte membrane.
[0018] A solid-state battery comprises the above-mentioned dry double-layer sulfide electrolyte membrane.
[0019] Beneficial effects of the present invention:
[0020] The present invention compounds a polymer protective layer on one side of the sulfide ion transport layer to repair microcracks on the surface of the sulfide ion transport layer, thereby avoiding defluorination reaction of polytetrafluoroethylene on the negative electrode side, and realizing the preparation of an electrolyte membrane with low thickness, complete structure, high ionic conductivity and stable interface.
[0021] Sulfide electrolytes are relatively active and are prone to react with solvents and binders, thereby affecting the ionic conductivity of the electrolyte membrane. The dry-process double-layer sulfide electrolyte membrane of the present invention does not introduce solvents, initiators, and highly active monomers during the preparation process, thereby ensuring the good performance of the dry-process double-layer sulfide electrolyte membrane of the present invention.
[0022] The dry double-layer sulfide electrolyte membrane prepared by the present invention not only solves the defect problem of microcracks generated in the current dry electrolyte membrane during hot rolling, but also can isolate the contact between the electrolyte membrane and the negative electrode plate, avoiding the reduction reaction of polytetrafluoroethylene at low voltage to affect the performance of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The figure is a flow chart of the preparation of dry double-layer sulfide electrolyte membrane;
[0024] Figure 2 This is a graph showing the cycle capacity retention rate of the solid-state battery in Example 1. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with the embodiments of the present invention and the accompanying drawings.
[0026] Example 1
[0027] The method for preparing the dry double-layer sulfide electrolyte membrane of Example 1 comprises the following steps:
[0028] 49.9 g of Li6PS5Cl powder and 0.1 g of polytetrafluoroethylene (PTFE) were mixed to obtain a mixed powder, the mixed powder was manually ground in a mortar for 30 min, polytetrafluoroethylene was subjected to fiberization treatment under high-intensity shear force, and a preliminary electrolyte sheet was prepared. The preliminary electrolyte sheet was placed in a roller press, the temperature of the upper roller and the lower roller of the roller press were set to 80 ° C, the rotation speed of the upper roller and the lower roller of the roller press were both 0.07 m / min, and the distance between the upper roller and the lower roller of the roller press was set from 200 μm, and each time it was reduced by 5 μm until the thickness of the preliminary electrolyte sheet was pressed to 25 μm, and the sulfide ion transport layer was obtained. To ensure the uniformity of the sulfide ion transport layer, each thickness was rolled 3 times.
[0029] 3.25g of polyethylene oxide (PEO) and 1.75g of LiTFSI were mixed and placed on the surface of a polytetrafluoroethylene membrane on a heating platform to heat and melt at 90°C. After 30 minutes, a polymer protective layer was obtained. The polymer protective layer and the sulfide ion transport layer were pressurized and composited to obtain a dry double-layer sulfide electrolyte membrane. The pressure was 3Mpa and the pressure holding time was 5min. The thickness of the polymer protective layer was 6μm. The molecular weight of polyethylene oxide was 150,000.
[0030] A solid-state battery comprises the dry double-layer sulfide electrolyte membrane of Example 1, a positive electrode sheet and a negative electrode sheet.
[0031] Preparation method of negative electrode sheet: 19.25g of nano silicon, 0.3g of polyacrylic acid (PAA), 0.2g of carboxymethyl cellulose (CMC), and 0.25g of carbon nanotubes (CNT) were mixed and stirred by double planetary stirring at 300rpm for 4h, and then stirred at 800rpm for 6h to obtain negative electrode slurry, and the negative electrode slurry was coated on the current collector with a scraper, and dried at 100℃ for 12h to obtain the negative electrode sheet, and the prepared negative electrode sheet was cut into discs with a diameter of 10mm for standby use. The solid content of the negative electrode slurry is 41%.
[0032] Preparation method of positive electrode sheet: NCM811, Li6PS5Cl, CNT and PTFE are mixed in a mass ratio of 82:15:1.5:1.5 and then ground in an agate mortar for 40 minutes to obtain positive electrode active material, and the positive electrode active material is hot rolled to obtain a positive electrode active material layer at a rolling temperature of 120°C. After rolling, the thickness is 120 μm and the surface capacity is 6 mAh / cm 2 The prepared positive electrode active material layer and aluminum foil are compounded to prepare a dry-process positive electrode sheet.
[0033] Cell assembly: The prepared positive electrode sheet, the dry double-layer sulfide electrolyte membrane of Example 1, and the negative electrode sheet are stacked in sequence, and then packaged with aluminum-plastic film and the tabs are welded to prepare a solid-state cell. The polymer protective layer is close to the negative electrode sheet.
[0034] Example 2-3
[0035] The preparation method of the dry double-layer sulfide electrolyte membrane of Example 2-3 is substantially the same as that of Example 1. The difference between the preparation method of the dry double-layer sulfide electrolyte membrane of Example 2-3 and that of Example 1 is that the thickness of the sulfide ion transport layer of the dry double-layer sulfide electrolyte membrane of Example 2 is 10 μm, and the thickness of the polymer protective layer is 15 μm; the thickness of the sulfide ion transport layer of the dry double-layer sulfide electrolyte membrane of Example 3 is 80 μm, and the thickness of the polymer protective layer is 2 μm.
[0036] Example 4
[0037] The preparation method of the dry double-layer sulfide electrolyte membrane of Example 4 is substantially the same as that of Example 1. The difference between the preparation method of the dry double-layer sulfide electrolyte membrane of Example 4 and that of Example 1 is that the sulfide electrolyte in Example 4 is Li 10 GeP2S 12 .
[0038] Example 5
[0039] The preparation method of the dry double-layer sulfide electrolyte membrane of Example 5 is substantially the same as that of Example 1. The difference between the preparation method of the dry double-layer sulfide electrolyte membrane of Example 5 and Example 1 is that the mass of the Li6PS5Cl powder in Example 5 is 47.5 g, and the mass of polytetrafluoroethylene is 2.5 g.
[0040] Embodiment 6-7
[0041] The preparation method of the dry double-layer sulfide electrolyte membrane of Examples 6-7 is substantially the same as that of Example 1. The difference between the preparation method of the dry double-layer sulfide electrolyte membrane of Examples 6-7 and Example 1 is that the grinding time of the mixed powder in Example 6 is 10 min; the grinding time of the mixed powder in Example 7 is 90 min.
[0042] Embodiment 8-9
[0043] The preparation method of the dry double-layer sulfide electrolyte membrane of Examples 8-9 is substantially the same as that of Example 1. The difference between the preparation method of the dry double-layer sulfide electrolyte membrane of Examples 8-9 and that of Example 1 is that the melting temperature in Example 8 is 60°C, and the melting temperature in Example 9 is 120°C.
[0044] Comparative Example 1
[0045] The preparation method of the double-layer sulfide electrolyte membrane of Comparative Example 1 comprises the following steps:
[0046] Preparation of sulfide ion transport layer: 0.5 g of polyvinylidene fluoride was dissolved in 55 g of toluene and stirred at 60 ° C for 4 h. After the polyvinylidene fluoride was completely dissolved, 49.5 g of Li6PS5Cl electrolyte powder was added. After vacuum stirring at 400 r / min for 30 min, a uniform electrolyte slurry was formed. The electrolyte slurry was coated on the substrate PET by cast coating and dried at 100 ° C for 12 h. The thickness of the electrolyte sheet was 25 μm.
[0047] Preparation of polymer protective layer: 3.25 g of PEO and 1.75 g of LiTFSI were dissolved in anhydrous acetonitrile, stirred at 50°C for 4 h to form a uniform solution, and then coated on the surface of a glass plate by a casting method. After drying at 60°C for 8 h, the polymer protective layer was torn off from the glass plate to obtain the polymer protective layer.
[0048] Preparation of double-layer sulfide electrolyte membrane: The sulfide ion transport layer and the polymer protective layer are stacked in sequence, and the temperature of the upper and lower rollers in the roller press is set to 70°C. Hot pressing and compounding are performed to prepare a double-layer electrolyte membrane comprising a 25μm sulfide ion transport layer and a 6μm polymer protective layer.
[0049] Comparative Example 2
[0050] The preparation method of the sulfide electrolyte membrane of Comparative Example 2 is substantially the same as that of Example 1. The difference between the preparation method of the sulfide electrolyte membrane of Comparative Example 2 and Example 1 is that the sulfide electrolyte membrane of Comparative Example 2 is not provided with a polymer protective layer, and the thickness of the sulfide ion transport layer is 30 μm.
[0051] Comparative Example 3
[0052] The preparation method of the electrolyte membrane of Comparative Example 3 is substantially the same as that of Example 1. The difference between the preparation method of the electrolyte membrane of Comparative Example 3 and Example 1 is that the electrolyte membrane of Comparative Example 3 does not have a sulfide ion transport layer, and the thickness of the polymer protective layer is 30 μm.
[0053] AC impedance and cycle tests were performed on 1Ah cells using the electrolyte membranes of Examples 1-9 and Comparative Examples 1-3. The cycle test conditions were +0.5C / -0.5C@25°C. The test results are shown in Table 1.
[0054] Table 1 Test results of 1Ah cells using electrolyte membranes of Examples 1-9 and Comparative Examples 1-3
[0055]
[0056] Through the test results of Example 1 and Comparative Example 1, it can be obtained that the conductivity and cycle performance of the double-layer sulfide electrolyte membrane prepared by the dry method are better than those of the double-layer electrolyte membrane prepared by the wet method. The main reason is that the double-layer sulfide electrolyte membrane prepared by the dry method avoids the influence of the solvent on the sulfide electrolyte in the slurry stage of the wet process. By comparing the test results of Example 1 and Comparative Examples 2 and 3, it can be obtained that the structure of the dry double-layer sulfide electrolyte membrane not only maintains a relatively high ionic conductivity, but also avoids the reaction of polytetrafluoroethylene in the sulfide ion transport layer at low potential, thereby affecting the first effect and cycle stability.
Claims
1. A method for preparing a dry double-layer sulfide electrolyte membrane, characterized in that: The polymer protective layer and the sulfide ion transport layer are compounded under pressure to obtain the polymer protective layer, and the polymer protective layer is obtained by mixing a polymer and a lithium salt and then heating and melting them.
2. The method for preparing a dry double-layer sulfide electrolyte membrane according to claim 1, characterized in that: The thickness of the polymer protective layer is 1 to 25 μm, and the thickness of the sulfide ion transport layer is 10 to 80 μm.
3. The method for preparing a dry double-layer sulfide electrolyte membrane according to claim 1, characterized in that: The polymer is one or more of polyethylene oxide, polycaprolactone, polymethyl methacrylate, and polyurethane, and the mass ratio of the polymer to the lithium salt is 50-80:20-50.
4. The method for preparing a dry double-layer sulfide electrolyte membrane according to claim 1, characterized in that: The heating and melting temperature is 60-120° C., and the pressure of the pressurized compounding is 0.2-10 MPa.
5. The method for preparing a dry double-layer sulfide electrolyte membrane according to claim 1, characterized in that: The preparation method of the sulfide ion transport layer is as follows: sulfide electrolyte powder and a dry binder are mixed to obtain a mixed powder, the mixed powder is subjected to grinding and fiberization treatment to obtain a preliminary electrolyte sheet, and the preliminary electrolyte sheet is rolled by a roller press to obtain the sulfide ion transport layer.
6. The method for preparing a dry double-layer sulfide electrolyte membrane according to claim 5, characterized in that: The dry binder is polytetrafluoroethylene, and the mass ratio of the sulfide electrolyte powder to the dry binder is 95-99.99:0.01-5.
7. The method for preparing a dry double-layer sulfide electrolyte membrane according to claim 5, characterized in that: The temperature of the upper roller of the roller press is 60-150°C, and the temperature of the lower roller of the roller press is 60-150°C; the rotation speed of the upper roller of the roller press is 0.02-0.15m / min, and the rotation speed of the lower roller of the roller press is 0.02-0.15m / min; the distance between the upper roller of the roller press and the lower roller of the roller press gradually decreases; the grinding time is 10-90min.
8. The method for preparing a dry double-layer sulfide electrolyte membrane according to claim 5, characterized in that: The lithium salt is one or more of LiTFSI, LiFSI, LiPF6, LiClO4, LiBF4, LiAsF6, LiBOB, and LiODFB, and the sulfide electrolyte is Li2P2S6, Li7P3S 11 , Li3PS4, Li7PS6, Li4P2S6, Li2GeS3, Li4GeS4, Li2ZnGeS4, Li 4- 2x Zn x GeS4, Li5GaS4, Li 4+x+y (Ge 1-y-x Ga x )S4、Li 10 SiP2S 12 、Li6PS5K、Li 10 SnP2S 12 , Li 10 GeP2S 12 One or more of, K is a halogen.
9. A dry double-layer sulfide electrolyte membrane, characterized in that: The membrane is prepared by the method for preparing a dry double-layer sulfide electrolyte membrane according to any one of claims 1 to 8.
10. A solid-state battery, characterized in that: It comprises the dry double-layer sulfide electrolyte membrane according to claim 9.
Citation Information
Patent Citations
Double-layer sulfide electrolyte film and dry-wet mixing process preparation method
CN117832595A
Solid electrolyte membrane, preparation method and lithium ion battery
CN118016982A